Evaluation of forage sorghum cultivars in salt affected soils of Rio Grande do Norte, Brazil - Fernandes, Mário Bezerra; de Castro, Jadilson Rubens; Fernandes, Vera Lúcia Baima; de Aquino, Boanerges Freire; Alves, José Solon; de Góis, Francisco César (Pesquisa Agropecuaria Brasileira, 1994)
With the objective to evaluate the yield performance of sorghum (forage) cultivars grown on salt affected soils, a study was carried out during 1985-1988 in three different areas of the State of Rio Grande do Norte. The experiment consisted of seven treatments represented by sorghum (forage) cultivars IPA 493.5.1; IPA 469; IPA 02.215.1.1; IPA 485; IPA 1218; IPA 467 and ESAM 102, which were selected in the previous year, adapting an experimental layout in randomized block design with three replications. Statistical analysis revealed that some sorghum cultivars tested presented certain degree for salt tolerance, specially the IPA 1218 and ESAM 102, whereas the cultivar IPA 485 was found to be least tolerant. In terms of production, significant differences were verified concerning site, year and interactions.